Impaired endothelial antithrombotic activity following short-term interruption of continuous subcutaneous insulin infusion in type1 diabetic patients - Iorio, Alfonso; Federici, Marco Orsini; Mourvaki, Evangelia; Ferolla, Piero; Piroddi, Marta; Stabile, Anna; Timi, Alessandra; Celleno, Roberta; Benedetti, Massimo Massi (Thrombosis and Haemostasis, 2007)
Review of literature has shown an increased rate of thrombotic complications in diabetic patients with frequent episodes of hyperketonemia. However, the mechanisms by which ketosis promotes vascular disease in diabetic patients are unclear.It was the aim of this study to investigate early changes in haemostatic parameters and oxidative stress markers during the hyperketonemic status which follows the interruption of continuous subcutaneous insulin infusion (CSII) in type I diabetic patients. Eight CSII-treated type I diabetic patients underwent a 4-hour pump arrest. Blood glucose, insulin and 3-hydroxybutirate were measured to verify the metabolic response. A vein-occlusive (VO) test was performed for the determination of tPA and PAI-1 activities and their antigen levels before and after the CSII arrest. Coagulation factor VII and VIII were evaluated by one-stage PT and PTT method, respectively.TF, vWF, tPA and PAI-1 antigens were determined by ELISA, whereas tPA and PAI-1 activities using chromogenic methods. Plasma malondialdehyde (MDA) and protein carbonyl groups (PCG) levels were determined by HPLC and spectrophotometry, respectively. After the insulin deprivation phase, post-VO tPA antigen level significantly decreased (P=0.0391), whereas TF and post-VO PAI-1 activity and antigen levels significantly increased (P=0.0156 and P=0.0234, respectively). Plasma MDA and PCG levels were 1.88-fold and 1.74-fold higher than baseline values, respectively. In conclusion, the impairment of the fibrinolytic potential and the increases in TF, MDA and PCG levels may enhance the risk of both arterial and venous thrombosis during ketosis.Thus, early detection of hyperketonemia in DM patients could contribute to the prevention of life-threatening vascular events.
Keywords: Diabetes mellitus; fibrinolysis; hyperketonemia; oxidative stress; PAI-1